2008
DOI: 10.1103/physrevlett.100.254503
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Richtmyer-Meshkov Instability with Stereolithographed Interfaces

Abstract: A novel method to set highly accurate initial conditions has been designed in the context of shock tube experiments for the Richtmyer-Meshkov instability study. Stereolithography has been used to design the membrane supports which initially materialize the gaseous interface. The visualizations of both heavy-light and light-heavy sinusoidal interfaces were carried out with laser sheet diagnostics. Experiments are in very good agreement with theory and simulations for the heavy-light case, but probably due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 18 publications
2
41
1
2
Order By: Relevance
“…Figure 12-c shows that the computed interface overlaps the left boundary of the remnant zone. In earlier works [31], we showed that when a shock wave goes from an heavy gas to a light one, the membrane remmants are expelled ahead of the interface. In this heavy-to-light configuration, we also showed they have no influence on the interface dynamics.…”
Section: B Analysis Of the Experimental Picturesmentioning
confidence: 90%
“…Figure 12-c shows that the computed interface overlaps the left boundary of the remnant zone. In earlier works [31], we showed that when a shock wave goes from an heavy gas to a light one, the membrane remmants are expelled ahead of the interface. In this heavy-to-light configuration, we also showed they have no influence on the interface dynamics.…”
Section: B Analysis Of the Experimental Picturesmentioning
confidence: 90%
“…Subsequently, a novel technique was created by Jones & Jacobs (1997) and later adopted by others (Long et al 2009;Jacobs et al 2013) in a vertical shock tube in which the interface was generated by flowing light or heavy gas from opposite sides of the shock tube driven section and an initial 2D disturbance was realized by oscillating the shock tube at a prescribed frequency in the horizontal direction. In order to precisely control the initial 2D perturbation, Mariani et al (2008) used stereolithography to design the membrane supports which initially materialized the gaseous interface. Three-dimensional (3D) RMI was also studied by , who used the soap film technique to create a discontinuous gaseous interface with minimum surface feature and examined the 3D effect on the RMI.…”
Section: Introductionmentioning
confidence: 99%
“…The shapes of the gas interface in previous studies mainly include the single-mode interface (Meshkov 1969;Brouillette 2002;Jacobs & Krivets 2005;Mariani et al 2008;Long et al 2009;Balakumar et al 2012;, the spherical or cylindrical bubble formed by a soap film (Haas & Sturtevant 1987;Hosseini & Takayama 2005;Layes, Jourdan & Houas 2009;Haehn et al 2011Haehn et al , 2012Zhai et al 2011;Si et al 2012), the membrane-less gas cylinder (Jacobs 1992(Jacobs , 1993Tomkins et al 2008;Zhai et al 2014;Zou et al 2010) or gas curtain Orlicz et al 2009;Balakumar et al 2012;Balasubramanian et al 2012;Tomkins et al 2013) formed by the jet technique and the inclined planar interface (Wang et al 2012;McFarland et al 2014). Besides these classical interface shapes, Mikaelian (2005) theoretically and numerically studied the RMI on an initial interface with a discontinuous change in its first derivative.…”
Section: Introductionmentioning
confidence: 99%